Emerging Threats in Cybersecurity : A Deep Analysis of Modern Attack - Ashish Dewakar Pandey,; Shakil Saiyad, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This paper delves into the evolving landscape of cybersecurity threats, focusing on the latest attack vectors and techniques employed by malicious actors. With the rapid advancement of technology and increasing connectivity, the cybersecurity landscape is continuously evolving, presenting new challenges and threats to organizations and individuals alike. The analysis covers various modern attack methods, including but not limited to, ransomware, phishing, advanced persistent threats (APTs), and supply chain attacks. Each of these attack vectors is examined in detail, highlighting their characteristics, impact, and potential mitigation strategies. Furthermore, the paper discusses the role of emerging technologies such as artificial intelligence (AI) and the Internet of Things (IoT) in shaping the cybersecurity threat landscape. While these technologies offer numerous benefits, they also introduce new vulnerabilities that can be exploited by cybercriminals.
Keywords: Cybersecurity; Emerging Threats; Attack Vectors; Risk Mitigation; Countermeasures